(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
The aftermath of mass disasters presents a chaotic scene where the immediate identification of victims becomes a critical concern. Traditional methods of disaster victim identification (DVI) often confront numerous challenges, particularly when the remains are heavily fragmented, burned, or in a highly decomposed state. This review underscores the signif icant role of forensic radiology in the DVI process, offering a comprehensive examination of its applications, advance ments, limitations and future prospects. By integrating multiple studies and real-case applications, this review elucidates how forensic radiology has become instrumental in expediting accurate identifications, thereby aiding legal processes and providing closure to affected families.